Increased Cerebral Blood Flow Associated with Better Response Inhibition in Bipolar Disorder. (16th March 2015) - Dev, Sheena I.; McKenna, Benjamin S.; Sutherland, Ashley N.; Shin, David D.; Liu, Thomas T.; Wierenga, Christina E.; Eyler, Lisa T.
Abstract: Impairment on inhibitory tasks has been well documented in bipolar disorder (BD). Differences in cerebral blood flow (CBF) between BD patients and healthy comparison (HC) participants have also been reported. Few studies have examined the relationship between cognitive performance and regional CBF in this patient population. We hypothesized that group differences on an inhibitory task (the Delis-Kaplan Executive Function Scale's Color-Word Inhibition task) would be associated with differential CBF in bilateral anterior cingulate cortex (ACC), inferior parietal lobule (IPL) and dorsolateral prefrontal cortex (DLPFC) regions. Whole brain resting CBF was measured using Multiphase Pseudocontinuous Arterial Spin Labeling MR imaging for 28 euthymic BD and 36 HC participants. Total gray matter (GM) CBF was measured, and regional CBF values were extracted for each region of interest (ROI) using Freesurfer-based individual parcellations. Group, CBF, and group-by-CBF interaction were examined as predictors of inhibition performance. Groups did not differ in age, gender or education. BD patients performed significantly worse on Color-Word inhibition. There were no significant group differences in CBF in either total GM or in any ROI. There was a group by CBF interaction in the bilateral ACC, right IPL and right DLPFC such that better inhibitory performance was generally associated with higher resting state CBF in BD subjects, but not HC participants. Although CBF was not abnormal in this euthymic BD sample, results confirm previous reports of inter-episode inhibitory deficits and indicate that the perfusion-cognition relationship is different in BD compared to HC individuals. ( JINS, 2015, 21, 105–115)